Microbiological evaluation of meadow chernozem carbonate soil under various fertiliser systems - H. Motruk; O. Tonkha; O. Hryshchenko; O. Pikovska; Ya. Likar (Рослинництво та ґрунтознавство, 2021)
Microorganisms play an important role in shaping soil fertility, maintaining its performance as a bio-inert matter, and are an indicator of qualitative changes in the soil. As a result of anthropogenic impact on the soil, the number and species composition of the microbiota is decreasing. The purpose of the study was to assess the number of different physiological groups of microorganisms on meadow chernozem carbonate soil under different pea fertilisation systems. The number of different groups of soil microorganisms was estimated according to the method of D. H. Zvyagintsev by sowing soil suspension on solid culture media. It was found that the most favourable indicators of micro biocenosis and the highest yield of peas of the Tsarevych variety were formed by the residual effect of organic fertilisers and N45P45K45. The variant without fertilisers induces the development of organic matter mineralisation processes in meadow chernozem carbonate soil by the content of pedotrophic and humate-decomposing organisms and formed the lowest pea yield. The introduction of only mineral fertilizers for pea cultivation formed a high rate of humus accumulation at the level of Kac.= 1,6-1,9